Políticas públicas em saúde bucal com ênfase em má oclusão: análise comparativa entre duas escolas de educação básica do Tocantins, uma quilombola e uma periférica - Dias, Jessica Guimarães (Universidade Federal do Tocantins, 2021)
In Brazil, inequalities are evidenced by the exclusion of a significant portion of the population; this portion does not have access to the most basic social rights, including the right to health and quality of life. The insertion of oral health in the Brazilian health system (SUS) was a major milestone in public health, but the country exhibits a reality with high rates of dental problems, and the result is one of the most significant signs of social exclusion. The object of this research is oral health, with an emphasis on malocclusion and factors associated with it. The target of the research were students from two public schools - one from the remaining quilombola community of Santa Fé do Araguaia and the other from the peripheral community of Araguaína, both in the State of Tocantins, who were supposedly different with regard to access to health and policy development public health care. Therefore, the objective of this research was to know the oral health conditions, and the potential associated environmental and socioeconomic factors, thus discussing access to public policy in these locations, including Amartya Sem's theories on the guarantee of freedoms and well-being -Social. The study is of the transversal and analytical epidemiological type, using qualitative and quantitative research, young people aged between 12 and 19 years were evaluated, with 36 students from each school. The indices used were: DAI (Dental Aesthetic Index) and DMFT (Decayed, missed and filled teeth); we also apply socioeconomic questionnaires (the same used in SB Brasil 2010 and adapted by SB São Paulo-SP 2015), Food Security and Food Frequency. We obtained the following parameters: (1) prevalence, severity and need for orthodontic treatment; (2) the DMFT index; (3) the degree of food insecurity in the families of students and data on cariogenic diet; (4) impact of socioeconomic indicators on oral health and on the lives of these students (obtained through associative analyzes among the previous indexes); and (5) the implications of access to public policies on oral health. The results show the vulnerability in the access to oral health of students from both schools, and this factor is more significant in the school located in the quilombola community, in addition to inequities in public oral health policies. Even being in a city like Araguaína, the peripheries remain at a disadvantage in terms of assistance in oral health. The lack of perception regarding oral problems leads to the individual's “capacity”, which impairs their search for social well-being, this aspect is more significant in the school located in the quilombola community. The diet also significantly interferes with oral health problems. Therefore, the findings of the present study call attention to inequities in public policies, access and lack of perception by individuals. The methodology to measure access and perception used must be explored and applied in future studies. Furthermore, this study will possibly serve as a guide for managers regarding the evaluation of the effectiveness of public policies in oral health.